EFFORTS TO IMPROVE MATHEMATICS LEARNING RESULTS IN ALGEBRA MATERIAL USING THE SNOWBALL THROWING COOPERATIVE LEARNING MODEL IN CLASS VII STUDENTS - Andri Pratama; Syariful Fahmi (Universitas Ahmad Dahlan, 2020)
Based on the results of observations at Junior High School (SMP) Muhammadiyah 1 Mlati, it was found that students had difficulty understanding math problems, especially about algebraic material, so that students often made mistakes in solving the questions given, which were shown by achieving low scores and many who got scores below 60. This study aims to improve student learning outcomes in solving algebraic problems with the Snowball Throwing type cooperative learning model. This research is a Classroom Action Research (CAR) with the subject, namely students of class VII D SMP Muhammadiyah 1 Mlati with 32 students. The research object is learning mathematics with the Snowball Throwing type cooperative model. This study uses 3 data collection techniques, namely, observation, tests, and interviews. Observation is used as a guide for researchers in carrying out observation activities carried out to obtain data. The test was conducted to collect data and measure students' ability to solve math problems. Interviews were conducted to determine students' condition in the ongoing implementation of learning and their problems. This study obtained mathematics learning using the cooperative learning model type. Snowball Throwing received positive responses from students because students felt helped in learning mathematics to increase student learning outcomes.